Analysis of seepage through Al-Wand Dam by using SEEP/W ModelAnalysis of seepage through Al-Wand Dam by using SEEP/W Model - Jassama, Mahmood Gazey; Abdulrazzaqb, Sinan Salah (Anbar Journal of Engineering Sciences, 2020)
In geotechnical engineering, considered the seepage of water that occur through the soil medium is one of the important problems that must be accurately studied; therefor, knowledge of influencing factors on the value of seepage for the soil is a necessary when designing an earth dam. In this study seepage through Al-Wand dam was analyze by using SEEP/W model. It is a sub- program of Geo- Studio where it used to determine amount of seepage through the body of the dam and study the effect of the change of thickness of core and effect of construction without filter in amount of leakage. The results were that the quantity of leakage was small effected when reducing the thickness of core and when construct the Al-Wand dam without filter at different level of water in upstream.